Perfect Storm of Inpatient Communication Needs and an Innovative Solution Utilizing Smartphones and Secured Messaging - Patel, Neha; Siegler, James E.; Stromberg, Nathaniel; Ravitz, Neil; Hanson, C. William (Applied Clinical Informatics, 2016)
In hospitals, effective and efficient communication among care providers is critical to the provision of high-quality patient care. Yet, major problems impede communications including the frequent use of interruptive and one-way communication paradigms. This is especially frustrating for frontline providers given the dynamic nature of hospital care teams in an environment that is in constant flux.We conducted a pre-post evaluation of a commercially available secured messaging mobile application on 4 hospital units at a single institution for over one year. We included care providers on these units: residents, hospitalists, fellows, nurses, social workers, and pharmacists. Utilization metrics and survey responses on clinician perceptions were collected and analyzed using descriptive statistics, the Kruskal-Wallis test, and Mann-Whitney U test where appropriate.Between May 2013 and June 2014, 1,021 providers sent a total of 708,456 messages. About 85.5% of total threads were between two providers and the remaining were group messages. Residents and social workers/clinical resource coordinators were the largest per person users of this communication system, sending 9 (IQR 2–20) and 9 (IQR 2–22) messages per person per day, and receiving 18 (IQR 5–36) and 14 (IQR 5–29) messages per person per day, respectively (p=0.0001). More than half of the messages received by hospitalists, residents, and nurses were read within a minute. Communicating using secured messaging was found to be statistically significantly less disruptive to workflow by both nursing and physician survey respondents (p<0.001 for each comparison).Routine adoption of secured messaging improved perceived efficiency among providers on 4 hospital units. Our study suggests that a mobile application can improve communication and workflow efficiency among providers in a hospital. New technology has the potential to improve communication among care providers in hospitals.Citation: Patel N, Siegler JE, Stromberg N, Ravitz N, Hanson CW. Perfect storm of inpatient communication needs and an innovative solution utilizing smartphones and secured messaging.
Keywords: Communication; provider-provider interaction; mobile; secure texting; secure-messaging